Major arterial and venous thromboembolic complications in patients with COVID-19. (14th October 2021) - Lalor, N; Raffaeli, A; Bottini, F; Scapellato, J L; Banos, N; Pezzati, L; Intile, D; Longo, F
Abstract: Background: Cardiovascular complications; myocardial infarction (MI), ischemic stroke, and pulmonary embolism (PE), represent an important source of adverse outcomes in COVID-19 disease. Objectives: To evaluate the incidence of thromboembolic events, specifically PE, MI and stroke; risk factors, management patterns and outcomes in patients who tested positive for COVID-19 through RT-PCR in a regional hospital. Methods: We included 1125 adults patients admitted for COVID-19 infection between April 1 and October 30, 2020. The total cohort was analyzed by site of care: Intensive care (n=124) and nonintensive care (n=1001). Results: Cardiovascular risk factors prevalence in patients with COVID-19 were: hypertension (25.5%), hyperlipidemia (23.2%) and diabetes (12%). Prophylactic anticoagulation and therapeutic anticoagulation was prescribed in intensive care group (91.1% and 33.1%, respectively) versus (84.8% and 12.5%, respectively) in nonintensive care setting. Frequencies of major arterial or venous thromboembolism, pulmonary embolism and myocardial infarction were highest in the intensive care group (29%, 20% and 8%, respectively) than nonintensive care cohort (1.4%, 0.7% and 0, 5%, respectively). Hospital mortality was 29% in intensive care group and 1.3% in nonintensive care group. Conclusions: Patients admitted for COVID-19 had a high risk of major arterial or venous thromboembolism events, especially in the intensive care setting, despite the use of thromboprophylaxis with heparin. Funding Acknowledgement: Type of funding sources: None.